Characterization of broadband dielectric properties of aerosol-deposited Al2O3 thick films - Kwon, Oh Yun; Lee, Dong Won; Oh, Jong Min; Cai, Jangbom; Kim, Byung Sung (Journal of Ceramic Processing Research, 2018)
The dielectric properties of aerosol-deposited Al2O3 thick films were successfully investigated in broadband frequency ranges. Al2O3 thick films have been prepared through aerosol deposition on Cu substrate at room temperature. In order to measure the dielectric constants (εr) and dielectric losses (tanδ) at microwave frequency, a circular-patch capacitor (CPC) was formed on the Al2O3 films through the photo-lithography process. In order to evaluate the parasitic effect of the CPC structure based on measurement results, 3-D electromagnetic simulations were performed. After correction of the measured data including the parasitic components of the CPC, it was observed that the εr of the Al2O3 thick films slightly decreased with the increase in frequency from 9.7 at 1 GHz, different from the low-frequency results. The corrected tanδ of the Al2O3 thick films was 0.03 at 1 GHz and less than 0.05 up to 5 GHz.
Keywords: Aerosol-deposition; Al2O3 thick films; Characterization of dielectric properties; Microwave dielectric properties